2018
DOI: 10.1016/j.molmet.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

An intracrine view of sex steroids, immunity, and metabolic regulation

Abstract: BackgroundOver the past two decades, parallel recognition has grown of the importance of both sex steroids and immune activity in metabolic regulation. More recently, these discrete areas have been integrated in studies examining the metabolic effects of sex steroid immunomodulation. Implicit in these studies has been a traditional, endocrine model of sex steroid delivery from the gonads to target cells, including immune cells. Thus, research to date has focused on the metabolic effects of sex steroid receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 127 publications
(166 reference statements)
0
43
0
Order By: Relevance
“…Consistent evidence showed that E 2 reduces the uptake and favors the efflux of cholesterol by macrophages under inflammatory conditions, also by down-regulating the expression of scavenger receptors CD36 and SR-A (Allred et al, 2006;Corcoran et al, 2011;McCrohon et al, 1999;Napolitano et al, 2001;Rayner et al, 2008;Shchelkunova et al, 2013;Tomita et al, 1996;Vegeto et al, 2006;Wilson et al, 2008). Human and mouse macrophages were shown to express steroidogenic enzymes in vitro, depending on the tissue of origin (Rubinow, 2018).…”
Section: Hemostasis and Beyondmentioning
confidence: 90%
“…Consistent evidence showed that E 2 reduces the uptake and favors the efflux of cholesterol by macrophages under inflammatory conditions, also by down-regulating the expression of scavenger receptors CD36 and SR-A (Allred et al, 2006;Corcoran et al, 2011;McCrohon et al, 1999;Napolitano et al, 2001;Rayner et al, 2008;Shchelkunova et al, 2013;Tomita et al, 1996;Vegeto et al, 2006;Wilson et al, 2008). Human and mouse macrophages were shown to express steroidogenic enzymes in vitro, depending on the tissue of origin (Rubinow, 2018).…”
Section: Hemostasis and Beyondmentioning
confidence: 90%
“…In fact, extra-ovarian estrogen may play a role since the Cyp19a1 gene, which encodes for aromatase that mediates estrogen synthesis, is expressed in other tissues, especially the brain and adipose. Brain-produced estrogen may regulate GnRH neuron function ( 71 ), while estrogen synthesis in adipose tissue may regulate deposition in various depots ( 72 ). There are also profound sex differences in the immune system ( 73 ), metabolic rate and oxidative phosphorylation ( 74 ), fat deposition ( 69 ) and adipocyte number and size ( 75 ), all of which may or may not be dependent on sex steroids, gonadally or locally produced.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, sex steroids are synthesized de novo in the brain (neurons, glia), and hence their immunomodulatory effects can occur locally, representing paracrine and autocrine rather than classically endocrine effects (reviewed in ref. [299].…”
Section: Neural and Gene Network Functionmentioning
confidence: 99%